Tingkat Kejadian Respiratory Distress Syndrome (RDS) Antara BBLR Preterm Dan BBLR Dismatur - Meta Febri Agrina; Afnani Toyibah; Jupriyono Jupriyono (Jurnal Informasi Kesehatan Indonesia (JIKI), 2017)
Abstrak: There are many kind of low birth weight infant complication, one of them is RespiratoryDistress Syndrome (RDS). The aim of this research is to know the difference of RDS between preterm lowbirth weigth infant and dismature low birth weight infant. Research design use comparative analyticwith documentation study approach. Population of this research is all of the low birth weight infantwith RDS diagnose that registered in medical record of RSUD Kanjuruhan in 2016 period as many as 40infants. Sampling technique use simple random sampling as many as 36 respondent include. Statistictest use Fisher Exact which show us the result p > a (0,28 > 0,05), so this research accept H0, it meansthat there is no difference of RDS between preterm low birth weigth infant and dismature low birthweight infant.